1999
DOI: 10.1111/j.1559-1816.1999.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Are We Reluctant to Sell Friendship?1

Abstract: There are a number of indicators that people try to keep money out of social relationships, and a number of reasons why such separation might occur: undermining of intrinsic motivation, contamination of signals of friendship, and the apparently irrational tainting influence of money. Two experiments in which psychology students participated in brief conversations under various payment conditions found little evidence for payment adversely affecting the social interactions. A third study comparing a service gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Parents should watch television with their children to teach them how to interpret the media messages or the content of commercials. Parental supervision during watching enables the children to distinguish between reality and fantasy [7]. Several studies have documented that higher levels of screen time are associated with less sleep, more attention problems, and lower academic performance [8-10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Parents should watch television with their children to teach them how to interpret the media messages or the content of commercials. Parental supervision during watching enables the children to distinguish between reality and fantasy [7]. Several studies have documented that higher levels of screen time are associated with less sleep, more attention problems, and lower academic performance [8-10].…”
Section: Discussionmentioning
confidence: 99%
“…Falbe et al [19] showed that each hour-per-day screen time increase was associated with increased intake of total foods of low nutritional quality, increased intakes of sugar-sweetened beverages, fast food, sweets, and salty snacks, and decreased intakes of fruits and vegetables. It is important to encourage families to monitor their children’s media use and spend more time doing physical activities with their children to improve cardiovascular health in their adulthood [7]. There are contradictory results regarding the effect of electronic media use, and there is a two-sided coin that may affect both physical and psychological health [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If a person perceives that a relationship is based on a financial motive, he may evaluate the relationship as unsatisfactory because of the negative connotations of monetary exchange in the context of that relationship. For example, crucial emotional rewards may be less likely to occur when the relationship's existence is attributed to extrinsic motivation for the relationship partner (i.e., money) rather than intrinsic motivation (Kemp & Burt, 1999). In other words, if a consumer believes that a relationship exists with service providers only because they are being paid rather than based on a genuine affinity, then the consumer may perceive the relationship as less successful.…”
Section: Monetary Exchangementioning
confidence: 95%